A Strategy for Sustainable Development: Using Nanotechnology for Solar Energy in Buildings (Case Study Parand Town) - Jamal-e-Din Mahdi Nejad; Faezeh Asadpour (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Solar energy is a source of free and clean energy that has no harmful environmental effects. Simple applications of new technologies such as nanotechnology are a cost-effective way of using renewable energy, which has led many industries to invest in this area. In this descriptive-analytical study the utilization of solar energy in a hot and dry region of Iran was investigated as a useful and safe resource for supplying the energy needed for the construction of Parand town, considering the available climatic potentials. The statistical population in this study was a group of inhabitants of Parand town, employees of the Tehran Construction Engineering Organization and experts in the field, from which 384 participants were selected by simple random sampling. After collecting field information through a questionnaire, the relationships between the variables of the study were tested by SPSS. The result of the study showed that the most important achievements of using nanotechnology for solar energy in view of the sustainable development of building construction from the participants' perspective were photovoltaic coating on building roofs (58.7% of the participants' responses), nano solar water heaters (57.4% of responses) and active solar cell dryers (22.1% of responses) respectively.